Multi-Opinion Behavior in-Patient with Common Otolaryngological Procedures in Turkey - Selim Yıldırım, Yavuz; Cemal Yumuşakhuylu, Ali; Fatih Topuz, Muhammet (Journal of Otolaryngology Advances, 2016)
Background: Healthcare policies play an important role in the change of patient behaviours. Objective: Our objective with this study is to examine the patient behaviours and attitudes that have emerged following the changes in healthcare practices in Turkey. Study Design: prospective cross-sectional clinical inventory study Setting: Tertiary referral center Methods: This study was carried out in Istanbul. The study was conducted on patients who were operated at the ENT clinics. 413 patients from the Bezmialem Vakıf University, Hospital and 361 patients from the Marmara University Hospital were included in the study. Results: 320 of the patients included in the study were female with an average age of 38.12. The patients presented to 2.85 different hospitals before undergoing surgery, they were examined by 3.02 different ENT specialists before undergoing surgery and it took the patients 218.40 days to decide that they would undergo surgery. The period of time that elapsed before an appointment was scheduled for patients who decided to undergo surgery was 58.43 days. Conclusion: Considering that it is a necessity to have the opinion from a second physician for the patients to be operated, what should be the approach towards the patients who would like the opinions of a third and a fourth physician? Such patient behaviour is a pattern that has emerged on account of healthcare system changes.
Keywords: Second opinions; Ethics; Patient-physician.